Social conflict in the transforming society of the XXI century: general theoretical aspects - Asker Robertovich Kasparov (Вестник Майкопского государственного технологического университета)
The article notes that the large-scale transformations of the social system taking place in recent years inevitably affect the functioning of institutions, subsystems, the nature of social phenomena and processes, including significant impact on social conflict. Acting as an attributive characteristic of the society, the conflict is determined by the state of the social system itself, for example, it can become a consequence of its accelerated innovative development. According to many theoretical concepts of conflict, the factors of its determination are profound changes, as well as dysfunctions of the social system as a whole, its individual elements, etc. This is precisely the situation that is objectively developing in the transforming society of the 21st century. The formation of a new image of post-industrial society occurs under the influence of information and communication factors that go far beyond the narrow framework of the socio-technical environment and must be analyzed in the system of socio-cultural, civilizational coordinates. New elements of the social system replace the old ones, inevitably producing risks of innovative development. That is why the current conditions of the transforming society should be regarded as risky in terms of the genesis and development of conflicts. The current situation enhances the relevance of sociological knowledge of the conflict in the new conditions of the post-industrial society.